Efficient Organic Solar Cells with Non‐Fullerene Acceptors. Issue 37 (24th July 2017) - Li, Shuixing; Liu, Wenqing; Li, Chang‐Zhi; Shi, Minmin; Chen, Hongzheng
Abstract : Fullerene‐free OSCs employing n‐type small molecules or polymers as the acceptors have recently experienced a rapid rise with efficiencies exceeding 12%. Owing to the good optoelectronic and morphological tunabilities, non‐fullerene acceptors exhibit great potential for realizing high‐performance and practical OSCs. In this Review, recent exciting progress made in developing highly efficient non‐fullerene acceptors is summarized, mainly correlating factors like absorption, energy loss and morphology of new materials to their correspondent photovoltaic performance. Abstract : Fullerene‐free organic solar cells (OSCs) have made great progress in recent years with efficiencies surpassing 12%. In this Review, recent high‐performance non‐fullerene acceptors developed for OSCs are summarized, mainly correlating factors like absorption, energy loss and morphology of new materials to their correspondent photovoltaic performance. The perspectives for fullerene‐free OSCs with efficiency of 15% are briefly discussed.